Barcode implementation for staff and student tracing / Mohamad Zuki Abd Ghani - Abd Ghani, Mohamad Zuki (2005)
A web based Barcode Implementation for Staff and Student Tracing (BISST) prototype using PHP language, MySQL as database and apache as a server. This prototype seemed as tracing system. The purpose of this system is to provide a web based system that is capable to trace the location of lecturers and students in what class at Faculty of Information Technology and Quantitative Sciences (FITQS). The other purpose is provided a manageable attendance report for student and lecturer at FITQS in reporting manner. Prototyping is selected as the methodology in order to develop a prototype of BISST.